Scimitar syndrome – Uncommon variant with common presentation - Dave, Hitanshu Arunkumar; Parikh, Kathan Pareshkumar; Vasoya, Meghana Vijaykant (Indian Journal of Case Reports, 2020)
Scimitar syndrome, or congenital pulmonary venolobar syndrome, is a rare congenital heart defect characterized by the anomalous venous return from the right lung. A number of cases that lack all the features of a typical syndrome have been described as the scimitar variant, but the incidence is rare. These variants may be difficult to diagnose and, if diagnosed, they may not require surgical correction, instead, can be managed through episodic treatment and yearly monitoring for the development of complications. Herein, we report the case of a 9-month-old male baby with an uncommon variant of scimitar syndrome where the aortopulmonary collateral maintaining the blood supply of the right lung aroused from the right subclavian artery and descending thoracic aorta instead of inferior vena cava. Due to this, the management completely changed from catheterization of the heart to just follow-up monitoring of ventricular function and development of severe pulmonary hypertension.